Effectiveness of mangrove sword bean food bar addressed to older people of landslide disaster victims - Fatmah, Fatmah (Frontiers in Nutrition, 2024)
Background Older people require extra attention due to their reduced ability to prepare for disasters, as they adequately possess distinct needs. These groups necessitate uncomplicated, readily consumable, and palatable food options that fulfill their micronutrient needs. The objective of this research was to assess the effects of a snack bar enriched with api-api mangrove (Avicennia marina) and sword bean (Canavalia ensiformis) on the body weight and Body Mass Index (BMI) of older people individuals afflicted by a landslide event. Methods A non-randomized pre-post-intervention study was undertaken, involving 31 senior participants. The intervention group consisted of 15 seniors who were provided with a mangrove sword bean snack bar, while the control group comprised 16 seniors who received a sword bean food bar during 15 days. All study participants received education on maintaining a balanced diet for older people individuals. The data analysis involved using univariate and bivariate analyses, explicitly applying the independent t-test and dependent t-test. Results In the hedonic evaluation, the mangrove sword bean food bar had superior average attributes in terms of scent, flavor, texture, and color compared to the sword bean food bar. The consumption of snack bars made from mangrove sword beans resulted in a significant rise in weight (0.2 kg), energy intake (240.8 kcal), protein content (5.8 g), carbohydrate content (40.06 g), and fat content (4.4 g). Carbohydrate can significantly increase weight in the treatment subjects. Furthermore, the provision of comprehensive nutrition education has the potential to enhance the post-study knowledge score, as seen by the observed increase of 40.6. A significant disparity was observed between the mean carbohydrate consumption and understanding of balanced nutrition among the intervention and control groups. Conclusion Api-api mangrove sword bean snack bars have been identified as a viable and efficient substitute for emergency food provisions, particularly in disaster-stricken communities. These food bars have demonstrated a significant capacity to contribute to the weight gain of individuals within such groups, thus addressing the nutritional needs of impacted populations in the aftermath of natural calamities. Subsequent investigations may include employing pregnant women as participants to explore the issue above. Clinical Trial Registration Clinicaltrials.gov, identifier: NCT05897892.